The Use of Herbarium Media Assisted by Bigbook in Science Learning to Improve Students' Critical Thinking Ability - Muhammad Anwar Sani; Hamzan Hamzan (Journal of Educational Studies, 2026)
This research is motivated by the low critical thinking ability of fourth-grade students at MIN 1 Mataram City. Out of 30 students, 13 had low critical thinking skills. The purpose of this study was to improve students' critical thinking ability through the use of herbarium media assisted by a bigbook in class IV MIN 1 Mataram City in the 2025/2026 academic year. This type of research is classroom action research (CAR). The research setting was at MIN 1 Mataram City. The target of this research was to improve students' critical thinking ability through the use of herbarium media assisted by a bigbook. This research was conducted in two cycles, each cycle consisting of four stages: planning, implementation and observation, evaluation, and reflection. The instruments used were observation and tests. Data analysis was conducted qualitatively and quantitatively. The results showed that the use of herbarium media assisted by a bigbook could improve students' critical thinking ability. The average score of critical thinking skills increased from pre-action conditions of 40% to 63.33% in cycle I (good category), and 86.66% in cycle II (very good category). Teacher activities in learning increased from 68.05% in cycle I to 84.72% in cycle II, while student activities increased from 63.19% to 83.33%. This improvement includes aspects of solving problems clearly, directedly, and purposefully, being able to analyze and conclude ideas according to phenomena and events that occur, and being able to draw conclusions and solve problems systematically with valid opinions